2008
DOI: 10.1093/carcin/bgn084
|View full text |Cite
|
Sign up to set email alerts
|

Nickel compounds induce phosphorylation of histone H3 at serine 10 by activating JNK-MAPK pathway

Abstract: Nickel (Ni) is a known carcinogen, although the mechanism of its carcinogenicity is not clear. Here, we provide evidence that Ni can induce phosphorylation of histone H3 at its serine 10 residue in a c-jun N-terminal kinase (JNK)/stress-activated protein kinase (SAPK)-dependent manner. Ni induces the phosphorylation of JNK, with no effect on the phosphorylation states of the extracellular signal-regulated kinase (ERK) or p38 mitogen-activated protein kinases. An inhibitor of JNK eliminated the Ni-initiated JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 30 publications
2
55
1
1
Order By: Relevance
“…C2C12 thus appeared to be particularly prone to histone modifications triggered by short term tungsten-alloy exposure with minimal impact on cell viability. We did not detect any effect of nickel on H3-Ser10 phosphorylation as opposed to the previous study that reported nickel mediated increased H3-Ser10 phosphorylation in human lung carcinoma A549 cultures (Ke et al, 2008). Also, methylation levels at trimethyl-H3-Lys4 appeared to be unaffected in all our culture systems even at high concentrations of cobalt in contrast to increased methylation of H3-Lys4 reported in A549 cells (Li, xet al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…C2C12 thus appeared to be particularly prone to histone modifications triggered by short term tungsten-alloy exposure with minimal impact on cell viability. We did not detect any effect of nickel on H3-Ser10 phosphorylation as opposed to the previous study that reported nickel mediated increased H3-Ser10 phosphorylation in human lung carcinoma A549 cultures (Ke et al, 2008). Also, methylation levels at trimethyl-H3-Lys4 appeared to be unaffected in all our culture systems even at high concentrations of cobalt in contrast to increased methylation of H3-Lys4 reported in A549 cells (Li, xet al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…In animal experiments, injection of particulate nickel compounds (nickel sulfide or nickel subsulfide) into mice induced formation of malignant fibrous histiocytomas and sarcomas, with the p16 and Fhit genes often found to be epigenetically silenced in these cancers (9,10). Additional studies have demonstrated that nickel exposure caused truncation of histone H2B and H2A as well as global alterations of a variety of histone modifications, such as histone acetylation, methylation, phosphorylation, and ubiquitination (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, the underlying mechanisms responsible for these nickel-induced epigenetic alterations are poorly understood.…”
mentioning
confidence: 99%
“…The same cell cycle dependence of p-H3S10 was also demonstrated in plant and lower eukaryotic cells (7,8). In mammalian cells, H3S10 is primarily phosphorylated by Aurora B during mitosis (9), whereas its phosphorylation is regulated by c-Jun aminoterminal kinase/mitogen-activated protein (JNK/MAP) kinases when the cells are exposed heavy metals such as nickel (10).…”
mentioning
confidence: 99%